2018
DOI: 10.1016/j.psyneuen.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Stress hormones concentrations in the normal microenvironment predict risk for chemically induced cancer in rats

Abstract: Evidence show that stress hormones can influence cancer progression, but its role in carcinogenesis is poorly understood. In this study, we used a new method based on oral carcinogenesis model in rats to test the hypothesis that physiological levels of stress hormones in the normal tissue microenvironment would have significant predictive value for chemically induced cancer occurrence. Male Wistar rats were submitted to a tongue biopsy for measuring not-stress induced levels of norepinephrine, corticosterone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…In a previous study using an oral carcinogenesis model in rats, we demonstrated that increased pre-carcinogen NE concentrations in the normal tissue microenvironment were predictive for oral SCC occurrence, as well as lower expression of the tumor-suppressor gene pCDKN2a-p16. In addition, higher levels of NE in the tumor microenvironment were associated with lower immune response [ 53 ]. The presence of β-adrenergic receptors for NE and E has also been identified in HNSCC cell lines [ 18 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study using an oral carcinogenesis model in rats, we demonstrated that increased pre-carcinogen NE concentrations in the normal tissue microenvironment were predictive for oral SCC occurrence, as well as lower expression of the tumor-suppressor gene pCDKN2a-p16. In addition, higher levels of NE in the tumor microenvironment were associated with lower immune response [ 53 ]. The presence of β-adrenergic receptors for NE and E has also been identified in HNSCC cell lines [ 18 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…OS has been shown to play an important role in tumor initiation, promotion, and progression [67, 68] and is implicated in the pathogenesis of various biological systems and organs (reviewed lately by Kruk et al [77]). The role of PS in increased DNA damage has been supported by human studies, in vitro studies with animals, and cell lines exposed to stress hormones [14, 59, 113]. These multivariate complexities show the difficulty in determining and expressing the association between PS and cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that stress hormones were associated with cancer risk and progression, and SLC22A3 was associated with the transportation and reuptake of norepinephrine . The group of youngers or men may suffer a more stressful life due to various kinds of pressure from family or the society, where norepinephrine would be more generated.…”
Section: Discussionmentioning
confidence: 99%